Analysis of clothing microclimate conditions for lower body part workwear dedicated for motor impaired employees - Izabela Jasinska; Katarzyna Śledzińska; Violeta Jarzyna; Lidia Napieralska; Ewa Witczak (Communications in Development and Assembling of Textile Products, 2022)
Workwear dedicated for motor impaired employees was designed. The woven fabrics used meet the requirements for light to moderate effort according to PN-P-08525:1998, reaching suitable level of water vapor resistance meanwhile. The workwear’s design was carefully chosen to meet the requirements of motor impaired employees during their work activities. The analysis of microclimate was carried out to investigate the garment’s ability to transport water vapor outside from gaps between body part and item of clothing. Two sets of workwear were tested, showing that both garments’ construction and woven fabrics properties influence thereon.